Implementation of flutter in the development of an Android E-Commerce furniture application using the Sdlc Waterfall Method (A case study of mandiri furniture) - Umar Tsani Abdurrahman; Iskandar; Kuncoro Adin Nugraha (LPPMPK- Universitas Muhammadiyah Cileungsi, 2026)
The development of information technology encourages Micro, Small, and Medium Enterprises (MSMEs) to adapt to digital-based sales systems. Mandiri Furniture, as one of the MSMEs in the furniture sector, still faces problems in the marketing process, product ordering, and sales data management that are still carried out conventionally, resulting in low efficiency and limited market reach. This study aims to develop an Android-based e-commerce application that can increase sales efficiency and provide system convenience for users and admins. The research method used is the Software Development Life Cycle (SDLC) with the Waterfall model, which includes the stages of requirements analysis, system design, implementation, testing, and maintenance. The application was developed using the Flutter framework, MySQL database, and PHP as a link between the application and the server. Application Programming Interface (API) integration was carried out to support system functionality, including Stripe as a payment service, RajaOngkir for shipping cost calculations, and Imgur for uploading product images. System testing was carried out using the Blackbox Testing method and showed that all application features ran well on several tested Android devices. The results showed that the application was able to increase the efficiency of the sales process and ease of use of the system with a performance level of 75%. The implications of this research are expected to be a digital solution for MSMEs in increasing competitiveness, expanding market reach, and optimizing sales data management in an integrated manner